About The Problems of Types of Understanding Law - Vladimir Valentinovich Kozhevnikov (Britain International for Academic Research (BIAR-Publisher), 2025)
Noting that law is a highly multifaceted concept, this article focuses on the issue of types of legal understanding. Critically assessing the positions of Russian scholars on the classification of these types, the paper offers the author's perspective on this theoretical issue. It also critically analyzes the positions of theoretical scholars on the relationship between philosophical and natural law types of legal understanding, as well as the integrative type and broad understanding of law.